Key terms of the Qur'an : a critical dictionary - Sinai, Nicolai, 1976- (Princeton, New Jersey : Princeton University Press, 2023)
"A one-volume, single-authored reference book featuring scholarly essays on key terms that appear in the Qur'an"--
Introduction -- Conventions and style -- Dictionary entries -- Bibliography -- Index of Arabic lemmas arranged according to the English alphabet -- English index of Qurʼanic terms -- Index of Qurʼanic verses.
Includes bibliographical references and indexes.
Description based on online resource; title from digital title page (viewed on July 12, 2023).
JSTOR
Keywords: Qurʼan -- Dictionaries; Qurʼan -- Terminology; Qurʼan -- Language, style -- Terminology; Qurʼan; Islam -- Terminology; RELIGION / Islam / Koran & Sacred Writings; Islam; Electronic books; Dictionaries; Terminology